14-Day Nose-Only Inhalation Toxicity and Haber's Rule Study of NNK in Sprague-Dawley Rats. (30th July 2021) - Hu, Shu-Chieh; Min, Seonggi; Kang, Hyun-Ki; Yang, Dong-Jin; Lewis, Sherry M; Davis, Kelly J; Patton, Ralph E; Bryant, Matthew S; Sepehr, Estatira; Trbojevich, Raul; Pearce, Mason G; Bishop, Michelle E; et al.
Abstract: 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is one of the key tobacco-specific nitrosamines that plays an important role in human lung carcinogenesis. However, repeated inhalation toxicity data on NNK, which is more directly relevant to cigarette smoking, are currently limited. In the present study, the subacute inhalation toxicity of NNK was evaluated in Sprague Dawley rats. Both sexes (9–10 weeks age; 16 rats/sex/group) were exposed by nose-only inhalation to air, vehicle control (75% propylene glycol), or 0.8, 3.2, 12.5, or 50 mg/kg body weight (BW)/day of NNK (NNK aerosol concentrations: 0, 0, 0.03, 0.11, 0.41, or 1.65 mg/L air) for 1 h/day for 14 consecutive days. Toxicity was evaluated by assessing body and organ weights; food consumption; clinical pathology; histopathology observations; blood, urine, and tissue levels of NNK, its major metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), and their glucuronides (reported as total NNK, tNNK, and total NNAL, tNNAL, respectively); O 6 -methylguanine DNA adduct formation; and blood and bone marrow micronucleus frequency. Whether the subacute inhalation toxicity of NNK followed Haber's Rule was also determined using additional animals exposed 4 h/day. The results showed that NNK exposure caused multiple significant adverse effects, with the most sensitive endpoint being non-neoplastic histopathological lesions in the nose. The lowest-observed-adverse-effect level (LOAEL) was 0.8 mg/kg BW/day or 0.03 mg/L air for 1 h/day for both sexes. An assessment of Haber's Rule indicated that 14-day inhalation exposure to the same dose at a lower concentration of NNK aerosol for a longer time (4 h daily) resulted in greater adverse effects than exposure to a higher concentration of NNK aerosol for a shorter time (1 h daily).